2023
DOI: 10.1007/s00170-022-10791-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induced plastic strain on the porosity of PA12 printed through selective laser sintering studied by X-ray computed micro-tomography

Abstract: 3D printing is a widespread technology in different fields, such as medicine, construction, ergonomics, and the transportation industry. Its diffusion is related to the ability of this technique to produce complex parts without needing for assembly of different components or post-processing. However, the quality of the parts produced by additive manufacturing could be affected by the fabrication process, thus leading to the development of different kinds of defects such as porosity or inclusions. Understanding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Moreover, the authors found a skin that appears to be significantly denser compared to the internal region. Similar results were obtained by Ajoku et al [40], by Rouholamin and Hopkinson [41], and by Morano et al [42].…”
Section: Polyamide 12supporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the authors found a skin that appears to be significantly denser compared to the internal region. Similar results were obtained by Ajoku et al [40], by Rouholamin and Hopkinson [41], and by Morano et al [42].…”
Section: Polyamide 12supporting
confidence: 87%
“…As an example, Figure 4a reports a comparison between the porosity values obtained by various authors (Stichel et al [25], Dewulf et al [36], Morano et al [42], and Pavan et al [47]) with approximately equal ED values (ED = 3.4 ± 0.1 J/cm 2 ), while, in Figure 4b, the contribution of pores with a specific diameter on the total porosity can be observed. The average value of the measured porosity is equal to 3.5 ± 0.3%.…”
Section: Porosity and Pore Size Distribution Of Pa12mentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, the mechanical properties are also dependent on the internal structure of the sample, e.g., porosity or inner defects [ 36 , 37 ]. It is well known that parts obtained by additive manufacturing are characterized by the occurrence of internal porosity [ 38 , 39 , 40 , 41 , 42 ]. In a previous work by the authors [ 40 ], the inner morphology of 3D-printed dogbones fabricated using PA12 was examined, revealing a significant level of porosity at approximately 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, observable unmelted powder particles were believed to have a substantial influence on the porosity formation process. Typically, pores originate during the SLS printing process, as testified by different works [ 40 , 44 , 45 ]. Moreover, some big dimples originate after fracture due to the detachment of unmelted particles [ 43 ].…”
Section: Resultsmentioning
confidence: 99%